THE PROVERBS AND IDIOMS THAT USED IN ARABIC IMHALLAMI DIALECT AND THEIR COMPARISON WITH PROVERBS AND IDIOMS THAT USED IN ARABIC DIALECT OF SİİRT - Yaşar ACAT (Fırat University, 2019)
Proverbs are words that give a certain judgment , advice and left us from our ancestors and anonymous. Proverbs and idioms are important items between language and culture. Every society has unique proverbs and idioms. They give clues about the lifestyle, language, culture, morality and customs of the society. Anatolian geography has become a place where dozens of languages have been spoken and lived since the beginning of history. The unknown thing is that these lands have become a hiding place for many archaic languages and dialects. Undoubtedly, a significant part of this cultural heritage constitutes Arabic dialects spoken in Anatolia. The researches about the Anadolu Arabic with his different dialects and accents, have started recently. It is obvious that there are many similar and diffrent matters between the Mhallemi dialect which is spoken in Midyat and its surroundings and the Arabic dialect spoken in Siirt and its surroundings and also thought as a highly rooted dialects of Arabic. The proverbs and idioms, remained until today, of the Siirt Arabs and Mhallemies who live in two different parts in close proximity to each other of the Al-Jazeera region, give important clues to understand the degree of closeness between the two dialects of Anatolian Arabic. In this academic notice, we will compare the proverbs and idioms that are still used vividly in Midyat and its surroundings with the proverbs and phrases used in and around Siirt, and try to reveal their similar and different characteristics.